The Relation between Religion and Science in Decree of the Indonesian Ulema Council in a Pandemic - Nazaruddin Latif; Irma Mustika Sari (Journal of Transcendental Law, 2020)
This paper examines the relation between religion and science in decrees issued by the Indonesian Ulema Council in the field of religion, particularly regarding the implementation of worship for Muslims in Indonesia. The Indonesian Ulama Council has issued a decree which not only prioritizes the an sich religious approach but is also based on the results found by scientists and researchers who are concerned about studying the COVID-19 pandemic. Therefore, this paper looks at the decree of the Indonesian Ulema Council based on a bibliographic approach by making this decree as the main source. As a result, the decree issued by the Indonesian Ulema Council has implicitly linked religion and science.